Expression of Claudin-4 in Lung Ischemia-Reperfusion Injury in Experimental Lung Transplantation. Issue 1 (2nd January 2022) - Luna-Flores, Antonia; Olmos-Zuñiga, J. Raúl; Jasso-Victoria, Rogelio; Gaxiola-Gaxiola, Miguel; Aguirre-Pérez, Teresa; Ruiz, Victor; García-Torrentera, Rogelio; Silva-Martínez, Mariana; Zenteno, Edgar; Gutierrez-Ospina, Gabriel; Santillan-Doherty, Patricio
Abstract: During lung transplantation (LTx), the warm (WIT) and cold ischemia time (CIT) predispose to ischemia-reperfusion injury (LIRI) and the primary graft dysfunction (PGD). LIRI induces edema by changes in tight junctions (TJs) of pulmonary epithelial and endothelial cells. Claudin-4 (CLDN4) is a component of TJs that participates in edema resolution and has been used as an indicator of acute pulmonary damage. Objective: To assess the presence of CLDN4 in bronchoalveolar lavage fluid (BALF) and pulmonary tissue as an early indicator of LIRI and its relationship with changes in pulmonary physiology, edema formation and histology in an experimental porcine model of LTx with CIT of 50 min or 6 h. Methods: In 12 pigs, LIRI was produced by: group I ( n  = 6) LTx with 50 min of CIT (LTx-50 min-CIT); and group II ( n  = 6) LTx with 6 h of CIT (LTx-6h-CIT). The lung function, edema formation, macroscopic and microscopic changes were assessed. CLDN4 expression in BALF and pulmonary tissue were determined. Results: Both groups presented similar clinical, edema, and histological damage, as well as similar expression of CLDN4 in BALF and tissue ( p  > 0.05, RM-ANOVA). Conclusion: CLDN4 expressed in BALF and the pulmonary tissue during the first 5 h within 72 h of the PGD window are not associated by the deterioration of lung function, edema and lung histological injury, in LTx with CIT 50 min or 6 h, CLDN4 does not seem to be a valuable indicator of LIRI.